Pengaruh Model Problem Based Learning terhadap Hasil Belajar Operasi Pecahan di Kelas V SD - Febrina Suhada; Syafri Ahmad (Universitas Negeri Padang, 2022)
This study aims to determine the effect of the Problem Based Learning model on student learning outcomes on the material of addition and subtraction of two fractions with different denominators in grade V SD. This type of research is an experimental research in the form of a Quasi-Experimental Type Nonequivalent Control Group Design. The sampling technique was cluster random sampling. The data analysis technique in this study used the t-test. Based on the results of data analysis from hypothesis testing using t-test, it was obtained tcount = 2.9, while ttable was at a significant level of 0.05 and was 1.677, then it was obtained tcount> ttable, namely 2.9> 1.677 so that Ha was accepted or Ho was rejected. Thus, there is an effect of the Problem Based Learning model on learning outcomes of addition and subtraction of two fractions with different denominators in grade V elementary schools.